2020
DOI: 10.1097/mcp.0000000000000729
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and cancer: a complex relationship

Abstract: Purpose of review Obstructive sleep apnea (OSA) has been recognized as a risk factor for cancer mainly through hypoxia, based on studies that did not distinguish among cancer types. The purpose of this review is to discuss the most recent data on epidemiology and pathophysiology of the OSA–cancer association. Recent findings According to epidemiological studies, OSA may have different influences on each type of cancer, either increasing or decreasing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 69 publications
0
14
0
1
Order By: Relevance
“…Of note, AREG, ATF3, DUSP1 , and ZFP36 were all related to cancers or pathways in cancer, and numerous studies have reported a role for these genes in different tumors ( 51 54 ). OSA is a recognized risk factor for cancer, mainly through hypoxia ( 55 ), but the exact mechanisms remain unclear. Combined with findings from our current study, we speculate that AREG, ATF3, DUSP1 , and ZFP36 may serve as a bridge between cancer and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, AREG, ATF3, DUSP1 , and ZFP36 were all related to cancers or pathways in cancer, and numerous studies have reported a role for these genes in different tumors ( 51 54 ). OSA is a recognized risk factor for cancer, mainly through hypoxia ( 55 ), but the exact mechanisms remain unclear. Combined with findings from our current study, we speculate that AREG, ATF3, DUSP1 , and ZFP36 may serve as a bridge between cancer and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, recent studies have shown that OSA may exacerbate vascular senescence via oxidative stress-related pathways through exosomes, accelerate chromosomal aging as evidenced by shortened telomere length, and trigger a senescence-like phenotype in pre-adipocytes [ 35 , 36 , 37 , 38 ]. Abnormal activity of the core cell-cycle machinery represents a driving force of tumorigenesis, while OSA has been recognized as a risk factor for cancer growth and aggressiveness mainly through HIF-1α signaling, which controls the synthesis of molecules with effects on inflammation, immune surveillance, and cell proliferation [ 39 ]. OSA is independently associated with impaired endothelial function and atherosclerosis through inflammation, oxidative stress, autonomic nervous system activation, and platelet activation [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…(76) Recentemente a associação da AOS com câncer tem sido estudada, sendo que a gravidade da AOS e da hipoxemia noturna intermitente têm sido associadas a maior crescimento tumoral e agressividade, notadamente no melanoma. (77,78)…”
Section: Consequências Clínicasunclassified